2008
DOI: 10.1111/j.1365-2265.2007.03146.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel phenotypic expression associated with a new mutation in LMNA gene, characterized by partial lipodystrophy, insulin resistance, aortic stenosis and hypertrophic cardiomyopathy

Abstract: This patient shows a novel clinical form of FPLD2, due to a mutation affecting lamin A only, with cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
(121 reference statements)
1
24
0
1
Order By: Relevance
“…FPLD, characterized by loss of fat tissue from the extremities, excess fat accumulation on the face and neck, and insulin-resistant diabetes, is prevailingly due to mutations located to exon 8; hypertrophic cardiomyopathy and aortic stenosis have been also reported in FPLD patients (Araujo-Vilar et al, 2008). The C-terminal domain of the lamin A, where mutations causing FPLD are clustered, binds specifically to SREBP1 (Lloyd et al, 2002).…”
Section: Laminopathies and Lamin-associated Cell Signaling Pathwaysmentioning
confidence: 98%
“…FPLD, characterized by loss of fat tissue from the extremities, excess fat accumulation on the face and neck, and insulin-resistant diabetes, is prevailingly due to mutations located to exon 8; hypertrophic cardiomyopathy and aortic stenosis have been also reported in FPLD patients (Araujo-Vilar et al, 2008). The C-terminal domain of the lamin A, where mutations causing FPLD are clustered, binds specifically to SREBP1 (Lloyd et al, 2002).…”
Section: Laminopathies and Lamin-associated Cell Signaling Pathwaysmentioning
confidence: 98%
“…For example, the coexistence of EDMD2, CMD1A, and LGMD1B has been recognized within a family [27]. Moreover, some patients have been reported to carry features of more than one laminopathy phenotype, such as FPLD2 with cardiac involvement [28] or mandibuloacral dysplasia with myopathy [29]. These findings suggest that laminopathies are a complex group of multisystem disorders, whose phenotypes cannot be always considered as discrete entities, but rather show wide overlap, some individuals and families having features of several different laminopathies and some mutations causing diverse manifestations in different individuals [30].…”
Section: Short Story Of Diseases Related To the Nuclear Laminamentioning
confidence: 97%
“…These cases include: phenotypes combining clinical features of lipodystrophy presenting also variable combinations of skeletal and/or cardiac muscle alterations [28,64,65]; CMT2 axonal neuropathy phenotypes associated with myopathic features and cardiac disease [50]; phenotypes combining axonal neuropathy, partial lipodystrophy, and scapuloperoneal myopathy [51]; phenotypes combining early-onset myopathy and progeria [66]; phenotypes combining MAD and myopathy [29].…”
Section: Overlapping Phenotypesmentioning
confidence: 98%
“…Strikingly, in this patient, once hypercortisolism was cured, an abnormal fat distribution became more evident, although it was not as severe as observed in classical Dunnigan disease. This change in fat distribution was particularly intriguing because it highlighted important differences among LMNA mutations that cause FPLD (13). The R545H variant, previously associated with FPLD (7), caused severe metabolic syndrome with android fat distribution in this patient.…”
Section: Inflammatory Myopathy and Laminopathymentioning
confidence: 98%
“…Moreover, several patients with mutations outside the immunoglobulin-like fold of lamin A have lacked the typical FPLD2 phenotype but experienced insulin resistance (4). In addition, some cases of FPLD2 have been associated with heart conduction disorders, valvulopathies, and cardiomyopathy (12)(13)(14). Other authors have reported LMNA-associated complex phenotypes, including heart failure and limb-girdle muscular dystrophy, due to a Ser334del variant (15,16); muscular dystrophy, lipodystrophy, and cardiac rhythm disturbances related to a R527P variant (17); or FPLD, early heart failure, first-degree atrioventricular block, and late proximal muscle weakness due to a R28W variant (12).…”
Section: Discussionmentioning
confidence: 99%